Effect of Pretreatments on Wettability and Dyeing Property of Cotton Fibers in an Environmentally Friendly Dyeing System. Issue 5 (September 2021) - Tang, Wencheng; Pei, Liujun; Zhang, Hongjuan; Zhu, Lei; Wang, Jiping
To investigate the influence of cotton wettability on its dyeing properties in a silicone non-aqueous dyeing system, alkali pretreatment was performed before dyeing. The dyeing properties and dyeing kinetics of reactive dyes in the non-aqueous system and a conventional dyeing system were compared. Alkali pretreatment significantly improved the wettability of cotton fiber by removing wax and pectin. The adsorption rate of dye increased with increased cotton fiber wettability using the non-aqueous system, while it barely changed using the conventional system. Pseudo-second-order kinetics fit well with dye adsorption for both systems. Dye fixation improved by 30% at a concentration of 2% owf, along with better levelness and color depth of the dyed cotton fiber, using the silicone non-aqueous system without salts and dispersants.